Linezolid-induced pancytopenia. (26th July 2018) - Leader, Ross; Hackett, James; Allan, Anne; Carter, Paul
Abstract : Linezolid is a bacteriostatic antibiotic of the Oxazolidinone class; it works by inhibiting the initiation of protein synthesis on bacterial ribosomes. Due to its excellent bioavailability after oral dosing, it has become an important tool in combating multi-drug-resistant bacteria including glycopeptide-resistant enterococci and methicillin-resistant Staphylococcus aureus . Side effects are multiple and potentially serious. We report the case of an 87-year-old man who developed pancytopenia secondary to a 6-week course of linezolid. Withdrawal of the antibiotic was decided as the treatment and resolution of the pancytopenia was evident within 2 weeks. Clinicians should be aware of this side effect of linezolid therapy and that weekly full blood count monitoring is paramount.